DEGREE OF GADGET USE AND SLEEP QUALITY AMONG FIRST-SEMESTER STUDENTS IN THE FACULTY OF PUBLIC HEALTH, NUSA CENDANA UNIVERSITY - Maria Magdalena Dwi Wahyuni; Angelina Kathlen Susanto; Marshanda Ananda Pandie; Melania Alpiani Derang Pehan; Santaliana Pakae; Yurihany Selsalia Jelita Ndolu (JURNAL WIDYA MEDIKA, 2026)
Quality of sleep is an essential aspect of health that is often compromised among first-year students due to lifestyle changes and excessive gadget use. This study aims to determine the relationship between gadget use intensity and sleep quality in first-year students at the Faculty of Public Health, Nusa Cendana University. An observational analytic study with a cross-sectional approach was conducted on 116 students from the class of 2025. Data were collected using validated questionnaires on gadget usage intensity (α = 0.872) and sleep quality (α = 0.795), analyzed using Spearman's Rho correlation. A positive and significant relationship was found between gadget usage intensity and sleep quality (r = 0.607; p < 0.001). Ordinal logistic regression showed that gadget usage intensity accounted for 50% of the variation in sleep quality. High gadget use intensity significantly correlates with poorer sleep quality. Academic institutions should implement digital curfews to help students manage sleep health during their academic transition.